Kajian Urgensi Undang Undang Pengelolaan Limbah Elektronik Upaya Mewujudkan Net Zero Emision - Rizky Zulkarnaen; Muhammad Hilqiya; Riska Indah Andini; Siska Sari; Yudi Widagdo Harimurti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores the urgency of enacting a specific Electronic Waste Management Law in Indonesia as a legal foundation to support the achievement of net zero emissions. Using a normative juridical approach, the research analyzes existing legal shortcomings, the application of the Extended Producer Responsibility (EPR) principle, and comparative insights from international e-waste regulatory frameworks. The findings indicate that current environmental regulations, such as Law No. 32 of 2009 on Environmental Protection and Management and Government Regulation No. 101 of 2014 on Hazardous Waste Management, do not explicitly regulate electronic waste. As a result, e-waste management remains fragmented and largely handled by the informal sector without adequate supervision or accountability mechanisms. Therefore, the establishment of a comprehensive E-Waste Law is crucial to enhance Indonesia’s legal structure, substantive norms, and legal culture in supporting a sustainable circular economy. Through the implementation of EPR and shared responsibility among producers, consumers, and government institutions, the law can function as a strategic tool to minimize electronic waste generation, improve recycling efficiency, and reduce carbon emissions. Such legal innovation would reinforce Indonesia’s environmental governance and accelerate progress toward its national goal of achieving net zero emissions by 2060.